Zinc and nano-ZnO – influence on living organisms - Mielcarz-Skalska, Lidia; Smolińska, Beata (Lodz University of Technology Press, 2017)
The use of zinc is very common in many industries. The multitude of advantages, and capabilities make use of different forms of penetration of zinc into the environment. Due to its ability to migrate, zinc is also accumulated in living organisms. Zn is an essential trace element but both the deficiency or excess are extremely dangerous for living organisms. Nowadays nanozinc has been increasingly used. Nanozinc is a component of daily used products, like plastics, ceramics, glass, cement, rubber, foods and many others. This leads to spreading nanozinc the environment with the possibility of its penetration into living organisms. This article is a review of the impact of zinc and zinc nanoparticles on a variety of organisms: ranging from microorganisms through plants and animals, to people.
Keywords: zinc; nano-ZnO influence; nano-zinc; zinc NPs; ecotoxicity; cynk; wpływ nano-tlenu cynku; nano cynk; nano cząsteczki cynku; ekotoksyczność